Crossing Segregated Boundaries Remembering Chicago School Desegregation - Danns, Dionne (Book collections on Project MUSE., 2020)
"Scholars have long explored school desegregation through various lenses, examining policy, the role of the courts and federal government, resistance and backlash, and the fight to preserve Black schools. However, few studies have examined the group experiences of students within desegregated schools. Crossing Segregated Boundaries centers the experiences of over sixty graduates of the class of 1988 in three desegregated Chicago high schools. Chicago's housing segregation and declining white enrollments severely curtailed the city's school desegregation plan, and as a result desegregation options were academically stratified, providing limited opportunities for a chosen few while leaving the majority of students in segregated, underperforming schools. Nevertheless, desegregation did provide a transformative opportunity for those students involved. While desegregation was the external impetus that brought students together, the students themselves made integration possible, and many students found that the few years that they spent in these schools had a profound impact on broadening their understanding of different racial and ethnic groups. In very real ways, desegregated schools reduced racial isolation for those who took part"--